Process‐based modeling of kilometer‐scale alongshore sandbar variability. Issue 8 (5th December 2014) - Walstra, D. J. R.; Ruessink, B. G.; Reniers, A. J. H. M.; Ranasinghe, R.
Abstract Subtidal nearshore sandbars may exhibit cyclic net offshore migration during their multi‐annual lifetime along many sandy coasts. Although this type of behavior can extend continuously for several kilometers, alongshore variations in cross‐shore bar position and bar amplitude are commonly observed. Alongshore variability is greatest when bars display km‐scale disruptions, indicative of a distinct alongshore phase shift in the bar cycle. An outer bar is then attached to an inner bar, forming a phenomenon known as a bar switch. Here, we investigate such large‐scale alongshore variability using a process‐based numerical profile model and observations at 24 transects along a 6 km section of the barred beach at Noordwijk, The Netherlands. When alongshore variability is limited, the model predicts that the bars migrate offshore at approximately the same rate (i.e. the bars remain in phase). Only under specific bar configurations with high wave‐energy levels is an increase in the alongshore variability predicted. This suggests that cross‐shore processes may trigger a switch in the case of specific antecedent morphological configurations combined with storm conditions. It is expected that three‐dimensional (3D) flow patterns augment the alongshore variability in such instances. In contrast to the observed bar behaviour, predicted bar morphologies on either side of a switch remain in different phases, even though the bars are occasionally located at a similar cross‐shore position. In short, the 1D model is not able to remove a bar switch. This data‐model mismatch suggests that 3D flow patterns are key to the dissipation of bar switches. Copyright © 2014 John Wiley & Sons, Ltd.